The Use of Lidocaine and Bupivacaine Mix in Adult Safe Male Circumcision: Less Is More. (9th March 2016) - Galukande, M.; Hodges, S.; Duffy, K.; Coutinho, A.; Kaggwa, S.
Abstract : Introduction . Lignocaine is (with or without bupivacaine) the only drug recommended for local anesthesia for safe adult male circumcision (SMC). This study evaluated the effectiveness of postoperative pain control when using two different concentrations. Methods . An observational analytical study conducted at an urban high volume site. Pain was assessed using the Visual Analogue Scale. Mixtures of lignocaine 2%, bupivacaine 0.5% (LiB), and water in ratios of 4 : 4 : 2 and 3 : 3 : 4 were compared. Results . Data from 217 clients were analyzed: 100 in the 4 : 4 : 2 group and 117 in the 3 : 3 : 4 group. Clients in the 4 : 4 : 2 group had more pain, at 60 minutes, compared to the 3 : 3 : 4 group (p = 0.035 ). The 3 : 3 : 4 mix used 70% less lignocaine and 90% less bupivacaine (60 mg and 15 mg); the allowable maximum dosages are 200 mg and 150 mg, respectively. Conclusion . The 3 : 3 : 4 mix was superior to the 4 : 4 : 2 mix. This has implications for supply chain management and potential reduction of LA toxicity. We therefore recommend the 3 : 3 : 4 mix for routine adult SMC.